Preparation process of Yellow River superfine sand 3D printing concrete material
By surface treatment of microcrystalline glass fine aggregates and reacting with sepiolite powder to form modified fine aggregates, and carbonization is carried out in a carbon dioxide atmosphere, the water leakage problem caused by the ultrafine sand of the Yellow River in concrete is solved, and the water leakage problem caused by the ultrafine sand in the Yellow River is improved. The extrusion properties and mechanical strength of concrete are obtained.
Patent Information
- Application Number
- CN202411682915.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-22
AI Technical Summary
Yellow River ultrafine sand is prone to water leakage when directly used to prepare concrete, resulting in the printed concrete structure being easily deformed or collapsed, and cannot meet the extrusion performance and shape stability requirements of 3D printed concrete.
The modified fine aggregate is formed by surface treatment of the microcrystalline glass fine aggregate and heated with the sepiolite powder in water. The carbonization process is then performed in a carbon dioxide atmosphere, and the fine aggregate is further modified to improve its water absorption and extrusion properties.
It effectively overcomes the water leakage phenomenon caused by ultra-fine sand in the Yellow River, improves the extrusion performance of concrete and the shape stability after printing, and at the same time enhances the mechanical strength of concrete.
Smart Images

Figure CN119430803A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of 3D printing concrete, and in particular to a preparation process of a Yellow River ultrafine sand 3D printing concrete material. Background Art
[0002] The information disclosed in this background technology section is only intended to increase the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art that has been known to ordinary technicians in the field.
[0003] Traditional technology requires the assembly and dismantling of formwork and the pouring of concrete when building concrete structures, which not only requires a lot of manpower and material resources, but also has a long construction period, a large amount of labor, and high costs. 3D printing concrete is a rapid prototyping technology based on digital models that uses concrete materials to print layer by layer to build concrete structures. It has the advantages of being convenient, efficient, and mold-free, which helps to significantly save labor, shorten the construction period of concrete structures, and eliminate the production cost of formwork. In addition, since 3D printing concrete technology can be carried out 24 hours a day, it can significantly improve production efficiency.
[0004] A large amount of fine aggregate is required in 3D printed concrete to ensure the strength of the concrete structure after printing. These fine aggregates are usually natural river sand. However, with the large-scale mining of this non-renewable resource, the output of high-quality natural river sand has been unable to meet the growing demand, which has also caused the price to continue to rise. The Yellow River ultrafine sand is a kind of sand with a fineness modulus less than 0.6. It is as fine as flour, and the annual average sand transport of the Yellow River is as high as 1.6 billion tons. Therefore, the use of the Yellow River ultrafine sand not only helps to reduce a large amount of siltation, but also helps to alleviate the contradiction between the supply and demand of natural river sand. However, when the Yellow River ultrafine sand is directly used to prepare concrete, there is a phenomenon of water seepage, which makes the concrete structure after printing prone to deformation or even collapse. Summary of the invention
[0005] The present invention provides a preparation process of a Yellow River ultrafine sand 3D printing concrete material, which not only alleviates the bleeding phenomenon caused by the Yellow River ultrafine sand, but also enables the prepared concrete to have good extrusion performance and maintain a stable shape after printing. Specifically, the technical solution of the present invention is as follows.
[0006] A preparation process of Yellow River ultrafine sand 3D printing concrete material, comprising the following steps: (1) The microcrystalline glass fine aggregate is immersed in a sodium silicate or potassium silicate solution and heated and kept warm for surface treatment. After completion, the solid and liquid are separated and the obtained solid product is dried to obtain the pretreated fine aggregate.
[0007] (2) Dispersing the sepiolite powder and the pretreated fine aggregate in water, stirring and heating the water for reaction, and separating the fine aggregate after the reaction is completed to obtain modified fine aggregate a.
[0008] (3) The modified fine aggregate a is mixed with the liquid phase obtained by solid-liquid separation in step (1) to form a mixture, and then the mixture is placed in a carbon dioxide atmosphere for carbonization treatment. After completion, the mixture is heated to decompose the silicic acid therein into silicon dioxide, thereby obtaining the modified fine aggregate b.
[0009] (4) Using silicate cement, the modified fine aggregate b, Yellow River ultrafine sand, silica fume, water reducer, and fiber as raw materials, mixing them, adding mixing water and stirring evenly, the 3D printing concrete material is obtained.
[0010] Furthermore, in step (1), the material-liquid ratio of the microcrystalline glass fine aggregate to the sodium silicate or potassium silicate solution is 1g: 5-20ml. Optionally, the mass fraction of the sodium silicate or potassium silicate solution is 2-4%.
[0011] Furthermore, in step (1), the heating and heat preservation temperature is 60-80° C. and the time is 2-3 hours. Optionally, the particle size of the microcrystalline glass fine aggregate is 1-3 mm.
[0012] Furthermore, in step (1), the drying temperature is 50-80° C. and the drying time is 40-60 min.
[0013] Furthermore, in step (2), the sepiolite powder is 22-30% of the mass of the pre-treated fine aggregate. Optionally, the fineness of the sepiolite powder is 70-100 mesh.
[0014] Furthermore, in step (2), the ratio of the total amount of the sepiolite powder and pretreated fine aggregate to water is 1 g: 25-40 ml.
[0015] Furthermore, in step (2), the heating reaction temperature is 50-60° C. and the time is 6-8 hours.
[0016] Furthermore, in step (3), the ratio of the modified fine aggregate a to the liquid phase is 1 g: 1.5-3 ml.
[0017] Furthermore, in step (3), the carbonization treatment time is 1.5 to 2 hours.
[0018] Furthermore, in step (3), the heating treatment is carried out at a temperature of 180-250° C. and for a time of 1-2 hours.
[0019] Furthermore, in step (4), the ratio of each component in the raw material is Portland cement: modified fine aggregate b: silica fume: water reducing agent: fiber = 70-105 parts by weight: 150-200 parts by weight: 10-17 parts by weight: 1.1-2 parts by weight: 5-8 parts by weight. The Yellow River ultrafine sand is 15-20% of the modified fine aggregate b, and the water-cement ratio is 0.38-0.42.
[0020] Furthermore, in step (4), the water reducer includes any one of a polycarboxylate water reducer, a lignin sulfonate water reducer, a naphthalene water reducer, an aliphatic water reducer, and the like.
[0021] Furthermore, in step (4), the fiber includes at least one of polyethylene fiber, polypropylene fiber, polyvinyl alcohol fiber, basalt fiber, carbon fiber, etc. Optionally, the length of the fiber is 3-10 mm.
[0022] Compared with the prior art, the present invention has at least the following beneficial technical effects: The present invention uses microcrystalline glass as fine aggregate, and after treating the surface of the microcrystalline glass with a sodium silicate or potassium silicate solution, the Si-O-Si and Si-O-Al in the silicon-oxygen tetrahedron and aluminum-oxygen tetrahedron structures on the surface of the microcrystalline glass are depolymerized and broken to be converted into -Al(OH)2 and -Si(OH)3, so that the microcrystalline glass fine aggregate forms a modified surface. Then the present invention places the microcrystalline glass fine aggregate and sepiolite powder in water for heating reaction. During this process, the hydroxyl group (-OH) on the sepiolite reacts with -Al(OH)2 and -Si(OH)3 on the surface of the microcrystalline glass fine aggregate to form Si-O and Al-O bonds, so that the sepiolite powder is loaded on the surface of the microcrystalline glass fine aggregate to form a modified fine aggregate. Furthermore, the present invention absorbs the liquid phase containing sodium silicate or potassium silicate in the sepiolite powder and performs a carbonization treatment, so that the sodium silicate or silicic acid is converted into solid silicic acid and sodium carbonate, and at the same time, the residual liquid phase is utilized. After being heated and decomposed, the solid silicic acid is converted into silicon dioxide particles to form pretreated sepiolite micropowder loaded with active silicon dioxide and sodium carbonate, while achieving the absorption of carbon dioxide and reducing carbon emissions generated in the production of the cement components.
[0023] When the modified fine aggregate and the Yellow River ultrafine sand are used to prepare 3D printed concrete materials, on the one hand, the sepiolite on the surface of the fine aggregate has good water absorption capacity, which can effectively overcome the phenomenon of water seepage of concrete materials caused by the Yellow River ultrafine sand and microcrystalline glass fine aggregate. At the same time, in the process of extrusion printing of concrete materials, the sepiolite is squeezed and the moisture therein is released, so that the concrete material maintains good fluidity / printability. After printing, the sepiolite reabsorbs moisture to prevent the printed concrete structure from deforming under the action of its own weight. At the same time, the silica particles in the sepiolite on the surface of the modified fine aggregate can react with the calcium hydroxide produced by cement hydration to form a hydrated calcium silicate gelling component, which not only increases the content of the gelling component in the concrete structure, but also improves the bonding force between the microcrystalline glass fine aggregate and the concrete structure, thereby improving the mechanical strength of the 3D printed concrete structure. In addition, the sodium carbonate / potassium in sepiolite reacts with calcium hydroxide, a cement hydration product, to form calcium carbonate and sodium / potassium hydroxide. The calcium carbonate can play the role of a cementitious component of the calcium silicate hydrate formed by compacting the silicon dioxide particles. After entering the concrete, the sodium / potassium hydroxide performs alkali excitation on the silica fume, causing the silica fume to undergo a hydration reaction to form cementitious components such as calcium silicate hydrate, which helps to improve the mechanical properties of the concrete structure. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. The embodiments of the present invention are described in detail below in conjunction with the accompanying drawings, wherein: Figure 1 This is a concrete 3D printing effect diagram of Example 1 of the present invention; Figure 2 This is a compressive strength test diagram of Example 1 of the present invention; Figure 3 This is a rheological test diagram of Example 1 of the present invention. DETAILED DESCRIPTION
[0025] The present invention will be further described below in conjunction with specific examples. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or according to the conditions recommended by the manufacturer. Now the present invention will be further described in conjunction with specific embodiments.
[0026] Example 1 A preparation process for a Yellow River ultrafine sand 3D printing concrete material comprises the following steps: (1) Mix glass-ceramic fine aggregate with a particle size distribution between 1 and 2 mm and sodium silicate solution with a mass fraction of 3% at a ratio of 1 g:10 ml and stir evenly, then heat to 70°C and keep warm for 2.5 hours. After completion, filter out the solid matter and dry it at 60°C for 50 minutes to obtain the pretreated fine aggregate.
[0027] (2) Disperse the sepiolite powder with a fineness of 80 mesh and the pretreated fine aggregate into water and stir evenly, wherein the sepiolite powder accounts for 25% of the mass of the pretreated fine aggregate, and the total amount of sepiolite powder and pretreated fine aggregate and the ratio of water is 1g:30ml. Then heat to 60°C and keep warm for 7 hours. After completion, filter the fine aggregate to obtain modified fine aggregate a.
[0028] (3) The modified fine aggregate a and the liquid phase filtered out in step (1) are mixed in a ratio of 1 g:2 ml and stirred evenly. The obtained mixture is placed in a carbon dioxide atmosphere for carbonization treatment for 1.5 hours. After the carbonization treatment, the obtained mixture is heated to 220° C. and kept warm for 1 hour to obtain modified fine aggregate b.
[0029] (4) Take 100 parts by weight of 42.5 ordinary Portland cement, 180 parts by weight of the modified fine aggregate b prepared in this example, 29 parts by weight of Yellow River ultrafine sand (fineness modulus distribution between 0.2 and 0.4), 12 parts by weight of silica fume, 1.45 parts by weight of polycarboxylate water reducer, and 6 parts by weight of polyvinyl alcohol fiber with a length of 5 mm. Mix the above raw materials and add mixing water at a water-cement ratio of 0.4 and stir evenly to obtain 3D printing concrete material.
[0030] After the 3D printing concrete material of this embodiment is printed (such as Figure 1 After natural curing, the 3D printed concrete specimens were cut and the 28d compressive strength of the concrete specimens was tested according to the Standard for Test Methods for Physical and Mechanical Properties of Concrete (GB / T 50081-2019). Figure 2 The 3D printing concrete material prepared in this embodiment was tested for its water seepage rate according to the "Water seepage test for cement concrete mixture" (T0528-2005). The thixotropy of the 3D printing concrete material was tested using the Hake Mars40 rheometer of Thermo Fisher Scientific. Figure 3 The test results are shown in the following table.
[0031] Example 2 A preparation process for a Yellow River ultrafine sand 3D printing concrete material comprises the following steps: (1) Mix glass-ceramic fine aggregate with a particle size distribution between 1 and 3 mm and potassium silicate solution with a mass fraction of 4% at a ratio of 1 g:5 ml and stir evenly, then heat to 80°C and keep warm for 2 hours. After completion, filter out the solid matter and dry it at 50°C for 60 minutes to obtain the pretreated fine aggregate.
[0032] (2) Disperse 70-mesh sepiolite powder and the pretreated fine aggregate in water and stir evenly, wherein the sepiolite powder accounts for 22% of the mass of the pretreated fine aggregate, and the total amount of sepiolite powder and pretreated fine aggregate and the ratio of water is 1g:25ml. Then heat to 55°C and keep warm for 6 hours. After completion, filter the fine aggregate to obtain modified fine aggregate a.
[0033] (3) The modified fine aggregate a and the liquid phase filtered in step (1) are mixed in a ratio of 1 g:1.5 ml and stirred evenly. The obtained mixture is placed in a carbon dioxide atmosphere for carbonization treatment for 2 hours. After the carbonization treatment, the obtained mixture is heated to 180° C. and kept warm for 2 hours to obtain modified fine aggregate b.
[0034] (4) Take 70 parts by weight of 42.5 ordinary Portland cement, 150 parts by weight of the modified fine aggregate b prepared in this example, 22.5 parts by weight of Yellow River ultrafine sand (fineness modulus distribution between 0.2 and 0.4), 12 parts by weight of silica fume, 1.1 parts by weight of polycarboxylate water reducer, and 5 parts by weight of polypropylene fiber with a length of 10 mm. Mix the above raw materials and add mixing water at a water-cement ratio of 0.38 and stir evenly to obtain 3D printing concrete material.
[0035] The 28d compressive strength, water bleeding rate and thixotropy of the 3D printed concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1. The test results are shown in the following table.
[0036] Example 3 A preparation process for a Yellow River ultrafine sand 3D printing concrete material comprises the following steps: (1) Mix glass-ceramic fine aggregate with a particle size distribution between 1 and 3 mm and sodium silicate solution with a mass fraction of 2% at a ratio of 1 g:20 ml and stir evenly, then heat to 60°C and keep warm for 3 hours. After completion, filter out the solid matter and dry it at 80°C for 40 minutes to obtain the pretreated fine aggregate.
[0037] (2) Disperse 100-mesh sepiolite powder and the pretreated fine aggregate into water and stir evenly, wherein the sepiolite powder accounts for 30% of the mass of the pretreated fine aggregate, and the total amount of sepiolite powder and pretreated fine aggregate and the ratio of water is 1g:40ml. Then heat to 50°C and keep warm for 8 hours. After completion, filter the fine aggregate to obtain modified fine aggregate a.
[0038] (3) The modified fine aggregate a and the liquid phase filtered out in step (1) are mixed in a ratio of 1 g:3 ml and stirred evenly. The obtained mixture is placed in a carbon dioxide atmosphere for carbonization treatment for 2 hours. After the carbonization treatment, the obtained mixture is heated to 250° C. and kept warm for 1.5 hours to obtain modified fine aggregate b.
[0039] (4) Take 105 parts by weight of 42.5 ordinary Portland cement, 200 parts by weight of the modified fine aggregate b prepared in this example, 40 parts by weight of Yellow River ultrafine sand (fineness modulus distribution between 0.2 and 0.4), 17 parts by weight of silica fume, 2 parts by weight of sodium lignin sulfonate water reducer, and 8 parts by weight of basalt fiber with a length of 3 mm. Mix the above raw materials and add mixing water at a water-cement ratio of 0.42 and stir evenly to obtain 3D printing concrete material.
[0040] The 28d compressive strength, water bleeding rate and thixotropy of the 3D printed concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1. The test results are shown in the following table.
[0041] Example 4 A preparation process for a 3D printing concrete material of Yellow River ultrafine sand comprises the following steps: taking 100 parts by weight of 42.5 ordinary Portland cement, 180 parts by weight of microcrystalline glass fine aggregate with a particle size distribution between 1 and 2 mm, 29 parts by weight of Yellow River ultrafine sand (fineness modulus distribution between 0.2 and 0.4), 12 parts by weight of silica fume, 1.45 parts by weight of polycarboxylate water reducer, and 6 parts by weight of polyvinyl alcohol fiber with a length of 5 mm. After mixing the above raw materials, adding mixing water according to a water-cement ratio of 0.4 and stirring evenly, a 3D printing concrete material is obtained.
[0042] The 28d compressive strength, water bleeding rate and thixotropy of the 3D printed concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1. The test results are shown in the following table.
[0043] Example 5 A preparation process for a Yellow River ultrafine sand 3D printing concrete material comprises the following steps: (1) Disperse 100-mesh sepiolite powder and glass-ceramic fine aggregate with a particle size distribution of 1 to 3 mm into water and stir evenly, wherein the sepiolite powder accounts for 30% of the mass of the pretreated fine aggregate, and the total amount of sepiolite powder and pretreated fine aggregate and the ratio of water is 1 g: 40 ml. Then heat to 50°C and keep warm for 8 hours. After completion, filter the fine aggregate to obtain modified fine aggregate a.
[0044] (2) The modified fine aggregate a and a 2% by mass sodium silicate solution are mixed in a ratio of 1 g:3 ml and stirred evenly. The obtained mixture is placed in a carbon dioxide atmosphere for carbonization treatment for 2 hours. After the carbonization treatment is completed, the obtained mixture is heated to 250° C. and kept warm for 1.5 hours to obtain the modified fine aggregate b.
[0045] (3) Take 105 parts by weight of 42.5 ordinary Portland cement, 200 parts by weight of the modified fine aggregate b prepared in this example, 40 parts by weight of Yellow River ultrafine sand (fineness modulus distribution between 0.2 and 0.4), 17 parts by weight of silica fume, 2 parts by weight of sodium lignin sulfonate water reducer, and 8 parts by weight of basalt fiber with a length of 3 mm. Mix the above raw materials and add mixing water according to a water-cement ratio of 0.42 and stir evenly to obtain 3D printing concrete material.
[0046] The 28d compressive strength, water bleeding rate and thixotropy of the 3D printed concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1. The test results are shown in the following table.
[0047] Example 6 A preparation process for a Yellow River ultrafine sand 3D printing concrete material comprises the following steps: (1) Mix glass-ceramic fine aggregate with a particle size distribution between 1 and 3 mm and potassium silicate solution with a mass fraction of 4% at a ratio of 1 g:5 ml and stir evenly, then heat to 80°C and keep warm for 2 hours. After completion, filter out the solid matter and dry it at 50°C for 60 minutes to obtain the pretreated fine aggregate.
[0048] (2) Disperse 70-mesh sepiolite powder and the pretreated fine aggregate in water and stir evenly, wherein the sepiolite powder accounts for 22% of the mass of the pretreated fine aggregate, and the total amount of sepiolite powder and pretreated fine aggregate and the ratio of water is 1g:25ml. Then heat to 55°C and keep warm for 6 hours. After completion, filter the fine aggregate to obtain modified fine aggregate a.
[0049] (3) The modified fine aggregate a and the liquid phase filtered out in step (1) are mixed in a ratio of 1 g:1.5 ml and stirred evenly. The obtained mixture is then heated to 180° C. for 2 hours to obtain modified fine aggregate b.
[0050] (4) Take 70 parts by weight of 42.5 ordinary Portland cement, 150 parts by weight of the modified fine aggregate b prepared in this example, 22.5 parts by weight of Yellow River ultrafine sand (fineness modulus distribution between 0.2 and 0.4), 12 parts by weight of silica fume, 1.1 parts by weight of polycarboxylate water reducer, and 5 parts by weight of polypropylene fiber with a length of 10 mm. Mix the above raw materials and add mixing water at a water-cement ratio of 0.38 and stir evenly to obtain 3D printing concrete material.
[0051] The 28d compressive strength, water bleeding rate and thixotropy of the 3D printed concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1. The test results are shown in the following table.
[0052] Example 7 A preparation process for a Yellow River ultrafine sand 3D printing concrete material comprises the following steps: (1) Mix glass-ceramic fine aggregate with a particle size distribution between 1 and 2 mm and sodium silicate solution with a mass fraction of 3% at a ratio of 1 g:10 ml and stir evenly, then heat to 70°C and keep warm for 2.5 hours. After completion, filter out the solid matter and dry it at 60°C for 50 minutes to obtain the pretreated fine aggregate.
[0053] (2) Disperse the sepiolite powder with a fineness of 80 mesh and the pretreated fine aggregate into water and stir evenly, wherein the sepiolite powder accounts for 25% of the mass of the pretreated fine aggregate, and the total amount of sepiolite powder and pretreated fine aggregate and the ratio of water is 1g:30ml. Then heat to 60°C and keep warm for 7 hours. After completion, filter the fine aggregate to obtain modified fine aggregate a.
[0054] (3) The modified fine aggregate a and clean water are mixed in a ratio of 1 g:2 ml and stirred evenly. The obtained mixture is placed in a carbon dioxide atmosphere for carbonization treatment for 1.5 hours. After the carbonization treatment is completed, the obtained mixture is heated to 220° C. and kept warm for 1 hour to obtain modified fine aggregate b.
[0055] (4) Take 100 parts by weight of 42.5 ordinary Portland cement, 180 parts by weight of the modified fine aggregate b prepared in this example, 29 parts by weight of Yellow River ultrafine sand (fineness modulus distribution between 0.2 and 0.4), 12 parts by weight of silica fume, 1.45 parts by weight of polycarboxylate water reducer, and 6 parts by weight of polyvinyl alcohol fiber with a length of 5 mm. Mix the above raw materials and add mixing water at a water-cement ratio of 0.4 and stir evenly to obtain 3D printing concrete material.
[0056] The 28d compressive strength, water bleeding rate and thixotropy of the 3D printed concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1. The test results are shown in the following table.
[0057] Example 8 A preparation process for a Yellow River ultrafine sand 3D printing concrete material comprises the following steps: (1) Mix crushed stone fine aggregate with a particle size distribution between 1 and 3 mm and a sodium silicate solution with a mass fraction of 2% at a ratio of 1 g:20 ml and stir evenly, then heat to 60°C and keep warm for 3 hours. After completion, filter out the solid matter and dry it at 80°C for 40 minutes to obtain the pretreated fine aggregate.
[0058] (2) The modified fine aggregate a of Example 3 and the liquid phase filtered in step (1) of this example were mixed in a ratio of 1 g:3 ml and stirred evenly. The obtained mixture was placed in a carbon dioxide atmosphere for carbonization treatment for 2 hours. After the carbonization treatment, the obtained mixture was heated to 250° C. and kept warm for 1.5 hours to obtain modified fine aggregate b.
[0059] (3) Take 105 parts by weight of 42.5 ordinary Portland cement, 200 parts by weight of the modified fine aggregate b prepared in this example, 40 parts by weight of Yellow River ultrafine sand (fineness modulus distribution between 0.2 and 0.4), 17 parts by weight of silica fume, 2 parts by weight of sodium lignin sulfonate water reducer, and 8 parts by weight of basalt fiber with a length of 3 mm. Mix the above raw materials and add mixing water according to a water-cement ratio of 0.42 and stir evenly to obtain 3D printing concrete material.
[0060] The 28d compressive strength, water bleeding rate and thixotropy of the 3D printed concrete material prepared in this embodiment were tested by the same method as in the above embodiment 1. The test results are shown in the following table.
[0061] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process of Yellow River ultrafine sand 3D printing concrete material, characterized in that: The steps include: (1) The microcrystalline glass fine aggregate is immersed in a sodium silicate or potassium silicate solution and heated to perform surface treatment. After completion, the solid-liquid separation is performed and the obtained solid product is dried to obtain the pretreated fine aggregate; (2) dispersing the sepiolite powder and the pretreated fine aggregate into water, stirring and heating the water for reaction, and separating the fine aggregate after the reaction is completed to obtain modified fine aggregate a; (3) mixing the modified fine aggregate a with the liquid phase obtained by solid-liquid separation in step (1) to form a mixture, and then placing the mixture in a carbon dioxide atmosphere for carbonization treatment, and then heating the mixture to decompose the silicic acid therein into silicon dioxide, thereby obtaining modified fine aggregate b; (4) Using silicate cement, the modified fine aggregate b, Yellow River ultrafine sand, silica fume, water reducer, and fiber as raw materials, mixing them, adding mixing water and stirring evenly, the 3D printing concrete material is obtained.
2. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to claim 1 is characterized in that: In step (1), the material-liquid ratio of the microcrystalline glass fine aggregate to the sodium silicate or potassium silicate solution is 1g:5-20ml; Optionally, in step (1), the mass fraction of the sodium silicate or potassium silicate solution is 2-4%.
3. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to claim 1 is characterized in that: In step (1), the heating and heat preservation temperature is 60-80°C and the time is 2-3 hours; Optionally, in step (1), the particle size of the glass-ceramic fine aggregate is 1-3 mm; Optionally, in step (1), the drying temperature is 50-80° C. and the drying time is 40-60 min.
4. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to claim 1 is characterized in that: In step (2), the sepiolite powder is 22-30% of the mass of the pretreated fine aggregate; Optionally, in step (2), the fineness of the sepiolite powder is 70-100 mesh.
5. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to claim 1 is characterized in that: In step (2), the ratio of the total amount of the sepiolite powder and pretreated fine aggregate to water is 1 g: 25-40 ml.
6. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to claim 1, characterized in that: In step (2), the heating reaction temperature is 50-60° C. and the time is 6-8 hours.
7. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to claim 1, characterized in that: In step (3), the ratio of the modified fine aggregate a to the liquid phase is 1 g: 1.5-3 ml; optionally, in step (3), the carbonization treatment time is 1.5-2 hours.
8. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to claim 1, characterized in that: In step (3), the heating treatment is carried out at a temperature of 180-250° C. and for a time of 1-2 hours.
9. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to claim 1, characterized in that: In step (4), the ratio of each component in the raw materials is Portland cement: modified fine aggregate b: silica fume: water reducing agent: fiber = 70-105 parts by weight: 150-200 parts by weight: 10-17 parts by weight: 1.1-2 parts by weight: 5-8 parts by weight; the Yellow River ultrafine sand is 15-20% of the modified fine aggregate b, and the water-cement ratio is 0.38-0.
42.
10. The preparation process of the Yellow River ultrafine sand 3D printing concrete material according to any one of claims 1 to 9, characterized in that: In step (4), the water reducer includes any one of a polycarboxylate water reducer, a lignin sulfonate water reducer, a naphthalene water reducer, and an aliphatic water reducer; Optionally, in step (4), the fiber includes at least one of polyethylene fiber, polypropylene fiber, polyvinyl alcohol fiber, basalt fiber, and carbon fiber; Optionally, in step (4), the length of the fiber is 3 to 10 mm.
Citation Information
Patent Citations
Preparation method of wet-mixed mortar not prone to precipitation
CN108083728A
Glass ceramic and preparation method thereof
CN108328930A
Special binder for microcrystalline glass
CN111689748A
Preparation process of microcrystalline glass aggregate concrete
CN118255557A
Preparation method of red brick recycled aggregate 3D printing concrete material
CN118771821A
Cited By
High-impermeability and high-homogeneity cement-based repairing mortar material and preparation method thereof
CN120081636A